THE USE OF DIFFERENTIAL EVOLUTION TO DETERMINE MAXIMUM GENERATION AND LOAD VALUES IN THE DISTRIBUTION NETWORK - Eva Tratnik; Janez Ribič; Matej Pintarič; Miran Rošer; Gorazd Štumberger; Miloš Beković (Journal of Energy Technology, 2023)
By integrating renewable energy sources into the existing distribution network, the characteristics and local stability of the network is highly impacted. The network, which was built with the goal of a directed energy flow from large conventional sources connected to the transmission network via the distribution network to consumers, can change the direction of the energy flow. The adoption of environmental commitments and directives encourages the integration of local dispersed energy sources, which can worsen voltage conditions in the distribution network. To avoid excessive local production, distribution network operators must limit the installation of new generati on units, as it is necessary to take into account the quality of power supply by monitoring its network parameters, such as the appropriate voltage profi le and the rati o between acti ve and reacti ve power. On the other hand, excessive loads due to the mass transiti on of household heati ng and transport towards electricity can also pose a problem for high-quality electricity supply due to the excessive voltage drop. The arti cle presents an algorithm for determining the maximum size of unit producti on and the maximum load at a node in the distributi on network. Also demonstrated is the use of variable tap transformer technology, which adjusts the tap of the transformer to provide an appropriate voltage profi le in the network. The enti re analysis was performed on a model of a real medium-voltage network, in which solar and hydropower plants are already included. The model was verifi ed by comparing its calculated values with actual measurements. The goal was to determine the size of the unit’s maximum producti on, as well as the size of the maximum load, by using the diff erenti al evoluti on algorithm, while keeping voltage profi les within the permissible limits. The results of the analysis are presented in the article.